Anaesthetic management of neonate with giant occipital meningoencephalocele: case report - Pahuja, Heena Dinesh; Deshmukh, Shubhda R.; Palsodkar, Supriya R.; Lande, Surabhi A. (International Journal of Research in Medical Sciences, 2017)
Meningoencephalocele is herniation of cerebrospinal fluid, brain tissue and meninges through the skull defect. The anaesthetic management of occipital meningoencephalocele is challenging because of the difficulty in securing airway, prone position, blood loss and, perioperative care. The two major aims of the anaesthesiologists while caring for children with occipital encephalocoele intraoperatively are to avoid premature rupture of the encephalocoele and to manage a possible difficult airway due to restricted neck movement and inability to achieve optimal position for intubation of the trachea. We report a case of giant occipital meningoencephalocele presented for surgical excision. Perioperative management of patients with giant meningoencephalocele may be challenging for both anaesthesiologist and neurosurgeon. These patients must be managed closely with an interdisciplinary approach.